Inhibition of listeria monocytogenes in minas frescal cheese by free and nanovesicle-encapsulated nisin - Malheiros,Patrícia da Silva (2012)
The effectiveness of free and nanovesicle-encapsulated nisin to control Listeria monocytogenes in Minas Frescal cheese was investigated. Commercial nisin was encapsulated into liposomes of partially purified soy lecithin. Free (0.1 mg/mL and 0.25 mg/mL) and nanovesicle-encapsulated nisin (0.25 mg/mL) were applied onto the surface of cheese samples, and L. monocytogenes was inoculated before incubation at 6-8°C for 28 days. A bactericidal effect was observed with 0.25 mg/mL free nisin; a bacteriostatic effect was observed for liposome-encapsulated nisin and 0.1 mg/mL free nisin. Free nisin was more efficient than nisin-loaded liposomes in controlling L. monocytogenes. Possible reasons for this behavior, and also the significance of nisin to soft cheeses are discussed. Nisin acted as a suitable barrier within hurdle technology, potentially extending the shelf-life and safety of fresh cheeses.